Restoring biological width in crown-root fracture: A periodontal concern - Nandlal B; Daneswari V (Wolters Kluwer Medknow Publications, 2007)
A 10-year-old male child reported to J.S.S. Dental College and Hospital presenting with a vertical crown-root fracture of maxillary central incisor with a history of fall 10 days back. A new treatment protocol was attempted in contrary to various schools of thoughts of coronal fragment removal wherein fractured fragments were approximated and internally reinforced with latest technologies in adhesive dentistry, the goal was to save the tooth, restore its function and esthetics. This case presents the above mentioned philosophy.